1997
DOI: 10.1271/bbb.61.1957
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradabilities of Ethylenediamine-N,N′-disuccinic Acid (EDDS) and Other Chelating Agents

Abstract: Biodegradabilities of chelating agents were tested with activated sludge. Ethylenediaminetetraacetic acid (EDTA) remained intact in the effluent even after acclimation for 100 days, but propanediamine-N,N'-disuccinic acid (PDDS) and nitrilotriacetic acid (NTA) were biodegraded after acclimation for 5 and 23 days, respectively. Optical isomers of ethylenediamine-N,N'-disuccinic acid (EDDS) had different biodegradabilities: SS- and RS-isomers were susceptible to biodegradation, but the RR-isomer was resistant. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…However, in Soil acid , the aging effect of Zn-EDDS in the current crop resulted in greater Zn uptake and % Zn utilization than in the previous crop. This is in agreement with previous findings which showed that applying EDDS increased plant Zn contents (Takahashi et al, 1997;Ylivainio et al, 2006). However, in the current crop Zn-EDDS in Soil calc resulted in lower Zn uptake and % Zn utilization than in the previous crop.…”
Section: Flax Growth and Zn Uptakesupporting
confidence: 93%
See 1 more Smart Citation
“…However, in Soil acid , the aging effect of Zn-EDDS in the current crop resulted in greater Zn uptake and % Zn utilization than in the previous crop. This is in agreement with previous findings which showed that applying EDDS increased plant Zn contents (Takahashi et al, 1997;Ylivainio et al, 2006). However, in the current crop Zn-EDDS in Soil calc resulted in lower Zn uptake and % Zn utilization than in the previous crop.…”
Section: Flax Growth and Zn Uptakesupporting
confidence: 93%
“…Applying Zn-EDDS resulted in a high Zn availability during the growth period of the previous crop, especially in the acidic soil, but Zn availability declined in the following year. This effect may be due to the fact that EDDS is a biodegradable chelating agent in the soil and the [S,S]-isomer rapidly mineralizes in the soil (Takahashi et al, 1997). The Zn chelates applied in this study were of medium or high stability, and it can be assumed that Zn was transferred from the chelates to soil binding sites to provide the plant with an adequate Zn concentration under these conditions.…”
Section: Soil Zn Fractions and Available And Easily Leachable Zn Of Soilmentioning
confidence: 99%
“…Zinc applied with Zn-S,S-EDDS at a rate of 10 mg Zn kg produced the lowest value, reaching only 0.97%. According to Schowanek et al (1997) and Takahashi et al (1997), the [S,S]-isomer is subject to rapid and complete mineralization. Over the last few years, the use of some biodegradable chelating agents, such as EDDS (S,S ethylenediaminedisuccinic acid), has been proposed as a way of enhancing the uptake of heavy metals (Luo et al 2006;Grcman et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ethylenediamine-N, N'-disuccinic acid (EDDS) is a biodegradable alternative of EDTA and is its closest performing counterpart. EDDS is readily degraded and one of the more widely studied biodegradable chelating agents, it has seen some commercial application in the detergent industry as a replacement for EDTA [43][44][45] [46,47]. All works discussed in this paper consider only the [SS]-isomer when referring to EDDS.…”
Section: Introductionmentioning
confidence: 99%